Intraoperative Diagnosis: Imprint Cytology and Frozen Section in Ovarian Tumor, Averting Additional Surgery - Kiran Lanjewar; Sanjay Deotale; Sunita Vagha; Sudhanshu Dakre (Journal of Pharmacy and Bioallied Sciences)
A granulosa cell tumor (GCT) is a type of ovarian cancer that constitutes approximately 10% of all ovarian malignancies. In this case, a female patient with hypothyroidism and a history of irregular periods was diagnosed with polycystic ovarian disease (PCOD) after a radiological examination, which subsequently recommended surgery. Frozen section analysis and imprint cytology assisted in the intraoperative diagnosis of the tumor. These diagnostic tools helped adopt a minimally invasive surgery where only the affected ovary was removed, thus avoiding an extra surgical procedure. It is usually described as a low-grade cancer, but it can recur many years later. Therefore, repeated imaging and tumor markers should be used to monitor the patient after the treatment and ensure early detection of the relapse, thus improving the patient’s prognosis.